Research Highlight: Micro- and Nanotechnology for Isolation and Detection of Circulating Tumor Cells - Nguyen, Nam-Trung (Micro and Nanosystems, 2015)
Circulating tumor cells (CTC) are rare cells, which are shed from a heterogeneous primary tumor into circulation. Although there is only one CTC for every one billion peripheral blood cells, these cells spread the cancer through metastasis to secondary sites. Isolating and analyzing CTCs are challenging tasks that potentially can be solved with advances in micro- and nanotechnologies. Analyzing the isolated CTCs help to understand their role in the spreading of cancer and ultimately lead to successful treatment of the disease.
Keywords: deformability